IMPLEMENTASI PEMBIAYAAN KPR MURAHABAH DITINJAU DENGAN PSAK 102 PADA BANK MUAMALAT KCU GORONTALO - Nismawati Ali; Niswatin Niswatin; Nurhayati Panigoro (Department of Accounting, Faculty of Economics and Business, Universitas Tadulako, 2023)
This research aims to understand the implementation of home ownership credit (KPR) using murabahah contract in accoradance with PSAK 102 (Accounting Standars) at Bank Muamalat Main Branch Office (KCU) Gorontalo. This research subject is Bank Muamalat Main Branch Office (KCU) Gorontalo, and the research with data collection techniques, including observation, interviews, and documentation. This research employs qualitativbe research analysis. In conclusion, the implementation of home ownership credit (KPR) using murabahah at Bank Muamalat Main Branch Office (KCU) Gorontalo is in accordance with PSAK 102 (Accounting Standars), but there are still some differences compared to the provisions stated in PSAK 102. The implementation at Bank Muamalat Main Branch Office (KCU) Gorontalo allows discount to be given only based on the bank’s regulations, and these discounts are not explicitly stipulated in the contract. Additionaly, providing a down payment for murabahah financing is not obligatory, as the nature of the contract changes to musyarakah if a down payment is used